Voltage balancing of split inductor based flying capacitor multilevel converter - Chamathakundil, Sneha Raj (Nanyang Technological University, 2023)
Multilevel converters are gaining attraction as the new kind of power electronic converters for medium and high-power applications. They are widely accepted because of their unique features such as staircase waveform quality, lower harmonics, low switching frequency and small common mode voltage. Flying capacitor multilevel converter is gaining more attraction compared to Diode clamped multilevel converter because of its easier extension to a higher number of output voltage levels. But with higher levels, comes the shoot through issue caused by the simultaneous switching of complimentary switches, which can be avoided by providing proper dead time between each switch. However, providing dead time causes distortion and reduces voltage and current gain. Introducing a split inductor between upper and lower switches in a converter reduces the dead time and solves the shoot through issue. The voltage balancing across flying capacitors is another important factor to be considered. In this work, an active voltage balancing scheme is applied on a three phase four level split inductor flying capacitor converter and it is tested under different loading conditions. And the various modes of operation of the Split Inductor Flying Capacitor converter is also analyzed.